Tunisia - Development Policy Review : Towards Innovation-driven Growth - World Bank (World Bank, 2012)
Tunisia must move from a low value-added and low cost economy to a higher value-added, knowledge intensive economy in order to significantly reduce unemployment, its overriding challenge. This Development Policy Review (DPR) provides a discussion of the key issues and challenges that are involved in achieving this goal. Towards this end, it discusses trade integration, innovation policies and enabling environment reforms (macro stability, economic regulation and governance, financial sector and labor market reforms and capital account opening) that could facilitate the structural transformation of the economy. The DPR is organized as follows: chapter one reviews growth and employment outcomes and challenges; chapter two discusses the rationale for increasing the pace of structural transformation of the economy in order to boost growth and reduce unemployment; chapter three examines the strengths and weaknesses of Tunisia's innovation system and strategies and proposes reform options in light of the international experience; chapter four discusses key aspects of Tunisia's global integration that could further contribute to innovation and productivity growth; chapters five discusses the key improvement in the enabling environment needed to support innovation and productivity growth (economic regulation, education sector reforms, financial sector reforms and labor market); finally, chapter six discusses structural transformation issues in natural resource-intensive sectors and examine the specific sectoral reforms needed to address the trade-offs between several objectives, including growth and natural resources preservation.